The political economy of growth and distribution: A theoretical critique - Stefan Dietrich Josten; Achim Truger (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2003)
This paper reconsiders the political economy approach to growth and distribution according to which (1) rising inequality induces more government redistribution; (2) more government redistribution is financed by higher distortionary taxation; and (3) higher distortionary taxes reduce economic growth. We present a variety of theoretical arguments demonstrating that all three propositions may be overturned by simply changing an assumption in a plausible way or adding a relevant real-world element to the basal models. The political economy models of growth and distribution, as well as the specific inequality-growth transmission channel they propose, must therefore be assessed as overly simplistic and inadequate with respect to the issues studied.
Keywords: D72; D3; H2; O4; 330; Political Economy; Redistribution; Inequality; Economic growth; Wirtschaftswachstum; Einkommensverteilung; Public Choice; Einkommensumverteilung; Kritik; Theorie